2016
DOI: 10.1109/tnsre.2015.2476481
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Beta EEG Changes During Active, Passive Movement and Functional Electrical Stimulation of the Lower Limb

Abstract: A number of electroencephalographic (EEG) studies have reported on event-related desynchronization/synchronization (ERD/ERS) during active movements, passive movements, and the movements induced by functional electrical stimulation (FES). However, the quantitative differences in ERD values and affected frequency bands associated with the lower limb have not been discussed. The goal of this paper was to quantitatively compare the ERD patterns during active movement, passive movement and FES-induced movement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
2
39
0
2
Order By: Relevance
“…Recently, researchers have tried to optimize the stimulation parameters to improve the rehabilitation effect, enhancing the efficiency by using interphase intervals, 27 strengthening the intrinsic foot muscle 40 and inducing neural responses in the sensorimotor area. 41 Unlike other studies, we modulated the pulse waveform of the wide-pulse NMES and explored its effect on the stimulus efficiency of sensory axon activation, and this may provide experimental evidence for optimizing parameters of burst-modulated waveforms to enhance sensory fiber recruitment. Our results show that mWP stimulation on sensory axons exhibited a higher afferent volley (H-reflex) than did WP when the same charge was applied ( Figure 2A).…”
Section: Carrier Frequency Effect On Hrcmentioning
confidence: 99%
“…Recently, researchers have tried to optimize the stimulation parameters to improve the rehabilitation effect, enhancing the efficiency by using interphase intervals, 27 strengthening the intrinsic foot muscle 40 and inducing neural responses in the sensorimotor area. 41 Unlike other studies, we modulated the pulse waveform of the wide-pulse NMES and explored its effect on the stimulus efficiency of sensory axon activation, and this may provide experimental evidence for optimizing parameters of burst-modulated waveforms to enhance sensory fiber recruitment. Our results show that mWP stimulation on sensory axons exhibited a higher afferent volley (H-reflex) than did WP when the same charge was applied ( Figure 2A).…”
Section: Carrier Frequency Effect On Hrcmentioning
confidence: 99%
“…35,36 Whether the peripheral neuromuscular system has been influenced by these motor tasks in different ways has seldom been reported. The different brain activities during motor tasks such as active, passive, and imaginary motor task have been investigated and compared widely.…”
Section: Discussionmentioning
confidence: 99%
“…The different brain activities during motor tasks such as active, passive, and imaginary motor task have been investigated and compared widely. 35,36 Whether the peripheral neuromuscular system has been influenced by these motor tasks in different ways has seldom been reported. 11,37 The results of this study showed exactly in what manner the spatial heterogeneity and temporal kinetics of muscle oxygenation varied during these motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…功能性电刺激疗法是使用低频电流刺激失去神经控制的肌肉, 使其收缩, 以替代或矫正器官及肢 体已丧失的功能 [124] . 功能性电刺激广泛运用于恢复由于脊髓损伤 [125] 、头部损伤、脑卒中 [126] 以及 其他神经系统疾病引起的运动功能障碍, 提升生活质量 [127,128] . 例如, 脊髓损伤导致大脑动作指令无 法通过中枢神经传输到肌肉神经 [129] , 然而传入通路仍是完整的, 可通过刺激受影响的外周神经或肌 肉来改变感觉运动区域的功能连通性 [130] .…”
Section: 基于功能性电刺激的控制策略unclassified